Online tutoring in Classics: a way of familiarizing the students with the use of technologies in learning activities - D. Vlachopoulos; L. Gonzàlez Julià; P. Gómez Cardó (Ágora, 2010)
The aim of this paper is to describe the design of an online tutoring system for the ancient Greek language and present its preliminary results after a first pilot application at the University of Barcelona. The tutoring system we propose consists of consulting services 24/7, synchronous meetings between the online tutor and the students (individually or in groups) and asynchronous evaluation activities related to the face to face activities.